2014
DOI: 10.1007/978-1-4939-2272-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Getting Across the Cell Membrane: An Overview for Small Molecules, Peptides, and Proteins

Abstract: The ability to efficiently access cytosolic proteins is desired in both biological research and medicine. However, targeting intracellular proteins is often challenging, because to reach the cytosol, exogenous molecules must first traverse the cell membrane. This review provides a broad overview of how certain molecules are thought to cross this barrier, and what kinds of approaches are being made to enhance the intracellular delivery of those that are impermeable. We first discuss rules that govern the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
538
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 662 publications
(548 citation statements)
references
References 192 publications
(198 reference statements)
7
538
0
3
Order By: Relevance
“…Various factors could cause a lack of bioactivity including targeting of a nonfunctional site (binding has no downstream effect), inadequate cellular permeability, and compound localization to an undesired compartment. Chemotypes have been identified that improve cellular uptake,(70) including conjugation of polyarginine,(71) as well as those that influence localization. (72) Such data could be incorporated into a traditional medicinal chemistry approach or chemical similarity searching.…”
Section: Resultsmentioning
confidence: 99%
“…Various factors could cause a lack of bioactivity including targeting of a nonfunctional site (binding has no downstream effect), inadequate cellular permeability, and compound localization to an undesired compartment. Chemotypes have been identified that improve cellular uptake,(70) including conjugation of polyarginine,(71) as well as those that influence localization. (72) Such data could be incorporated into a traditional medicinal chemistry approach or chemical similarity searching.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Given that many of the drug targets are localized in the subcellular compartments, an efficient translocation of the particles across the cell membrane is essential to attain desired therapeutic outcomes. [12] Endocytosis provides a means of cellular uptake of polymersomes that cannot enter the cells by passive diffusion. [13,14] Polymersomes initiate endocytosis by forming contacts with cell surface receptors.…”
Section: Controlling Polymersome Sizementioning
confidence: 99%
“…C 10 to C 12 ) result in improved selectivities for bacterial membranes hinting at an amphiphilic “sweet spot” that can be further leveraged by structural modifications enabled by organic synthesis. We are also interested in investigating whether some QACs simply permeabilize the membrane as opposed to fully lysing the cell, and if this varies by QAC architecture; such experiments are precedented [22] and represent a future direction for our groups.…”
mentioning
confidence: 99%